2012
DOI: 10.2298/abs1202675g
|View full text |Cite
|
Sign up to set email alerts
|

The aphid fauna of Turkey: An updated checklist

Abstract: This study provides a comprehensive list of Turkey aphid fauna (Hemiptera: Aphididea). A total of 466 species and 12 subspecies belonging to 141 genera and 13 tribes, are listed. The list includes all records from 1903 to 2011. The family of Aphididae comprise the highest number of species (457), followed by Adelgidae (6) and Phylloxeridae (3), respectively. Inside Aphididae, the tribe of Macrosiphini is the richest group with 197 species, whereas the tribe of Cinarini has only one species. The number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 10 publications
0
20
0
4
Order By: Relevance
“…The aphid fauna of Turkey has been surveyed extensively starting in the first part of the 20 th century (Trotter 1903). However, the aphid species and host plants in some regions have not been fully established, and as result, it is likely that new and invasive species will be found in Turkey (Görür et al 2012;Şenol et al 2014;2015). In this study, the morphological characterizations of A. passeriniana as an aphid of S. officinalis in Turkey were reported.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…The aphid fauna of Turkey has been surveyed extensively starting in the first part of the 20 th century (Trotter 1903). However, the aphid species and host plants in some regions have not been fully established, and as result, it is likely that new and invasive species will be found in Turkey (Görür et al 2012;Şenol et al 2014;2015). In this study, the morphological characterizations of A. passeriniana as an aphid of S. officinalis in Turkey were reported.…”
Section: Introductionmentioning
confidence: 70%
“…This genus is easily found on shrubs and herbs, never on sedges (Cyperaceae), very rarely on grasses (Poaceae) and less on trees (Blackman and Eastop 2006). About 221 species from Aphis are reported in Europe (Nieto Nafría et al 2017), and 69 species are in Turkey (Görür et al 2012). In addition, this genus is mostly found in the northern hemisphere, and some native species also found in South America, New Zealand and Australia (Blackman and Eastop 2006;2018).…”
Section: Introductionmentioning
confidence: 99%
“…In Turkey, a total of 466 species and 12 subspecies belonging to 141 genera and 13 tribes are listed. The family Aphididae comprises the highest number of species (457), followed by Adelgidae (6) and Phylloxeridae (3), respectively (Görür et al, 2012). Myzus cerasi causes the leaves to curl and also transmits several nonpersistent viruses of nonhost plants including bean yellow mosaic virus, celery mosaic virus, onion yellow dwarf virus, and potato virus Y (Blackman and Eastop, 1984;Bokx and Piron, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The aphid studies carried out in recent years and the aphid fauna of our country has been shown to be represented by approximately 3 families, 141 genera and more than 550 species (Remaudiere et al, 2006;Akyıldırım et al, 2013;Görür et al, 2012;Görür et al, 2018).…”
Section: Introductionmentioning
confidence: 99%